Prevalence of Hypertension among Doctors Working in Rajshahi Medical College and Hospital - Barua, Anik; Mahmuda, Shahin; Hosna, Latifa; Ara Lipi, Effat; Akter Benu, Farjana (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Hypertension (HTN) is a major public health problem in developed and developing countries. This is associated with oxidative stress and also a common cause of Cardiovascular Disease (CVD) amounting to 30% of worldwide death rate. The main objective of this study was to find out the proportion of hypertension among doctors working in Rajshahi Medical College and Hospital. Materials and methods: A cross-sectional type of descriptive study was conducted in Physiology Department in collaboration with Biochemistry Department of Rajshahi Medical College, Rajshahi during period of January 2022 to December 2022. The sample size was 248 and purposive sampling technique was applied. Data were collected from the respondents through a semi-structured questionnaire after taking informed written consent. Results: The study was carried out on doctors aged 25-60 years where 126 (50.80%) were female and 122 (49.20%) were male. Among 248 respondents, 27% were hypertensive, 46% were pre-hypertensive and 27% were normotensive.Among the respondents, who were under antihypertensive medication, 23.08% were in uncontrolled state and respondents who were not under antihypertensive medication, 13.39% were newly diagnosed hypertensive. Risk factors such as prehypertension, less physical exercise, overweight and family history of hypertension, diabetes mellitus, coronary heart disease were very common among the doctors. Conclusions: The study showed that physicians had higher proportion of hypertension. Among the participants, there was an unexpectedly low awareness rate and inadequate blood pressure regulation Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 15-19